Pengaruh word of mouth terhadap keputusan pembelian produk scarlet whitening - Gabriela ayu Anggreni; Febrina Hambalah (Faculty of Social and Political Science, 2022)
ABSTRACTThe general purpose of this study is to determine the role of online communication in helping consumers make purchasing decisions. The specific purpose of this study was to determine the effect of word of mouth on purchasing decisions for Scarlett Whitening products on students from the faculty of Social and Political Sciences, Hang Tuah University, Surabaya.In this study, it was dominated by female respondents as many as 78% or 78 people while respondents who were male were 22% or 22 people. While based on the background there were 31 people or 31% from respondents who entered Hang Tuah University in 2016, 13 people or 13% from 2017 generation, 21 people or 21% from 2018 generation, 19 people or 19% from 2019 generation and 16 people or 16% from 2020 generation.The results of research, it can be concluded that there is an influence between word of mouth variables on purchasing decisions. Word of mouth has a positive and significant effect on purchasing decisions where in the T test it is known that the T count on the word of mouth variable (X1) is 10.802 while the T table is 1.983 and the significant value shows 0,00. Because T count is greater than T table and the significant value is below 0,05.Keywords : Word of Mouth, Scarlett Whitening, Purchasing Decisions